Macrophage-lymphocyte clustering in rheumatoid arthritis. Issue 1 (February 1975) - Webb, F W; Baker, M; Weisbart, R; Bluestone, R; Goldberg, L
Abstract : The cells in synovial fluid from patients with rheumatoid arthritis contain a small percentage of macrophages. Such macrophages were isolated and cultured alone and with homologous and heterologous lymphocytes for 24 hours, in an attempt to identify possible contact between living lymphocytes and macrophages. Such contact was found, with clustering of lymphocytes around macrophages, and was particularly well shown by scanning electron microscopy.